Multiple roles for TnpI recombinase in regulation of Tn5401 transposition in Bacillus thuringiensis - Baum, J.A; Gilmer, A.J; Mettus, A.M.L (Journal of Bacteriology, 1999)
Tn5401 is a class II transposable element derived from the gram-positive bacterium Bacillus thuringiensis. The 4,837-bp transposon encodes a Tn3-like transposase (TnpA) and an integrase-like recombinase (TnpI) and is notable for its unusually long 53-bp terminal inverted repeats (TIRs). The tnpA and tnpI genes are transcribed from a common promoter, designated P(R), that is subject to negative regulation by TnpI. The TIRs of Tn5401 each contain a 38-bp sequence that can be aligned with the 38- to 40-bp TIR sequences of Tn3-like transposons and an adjacent 12-bp sequence that binds TnpI. This unique juxtaposition of TnpA and TnpI binding sites suggests that TnpI may regulate the binding or catalytic activity of TnpA. The results of the present study indicate that TnpI, in addition to functioning as a site-specific recombinase and as a transcriptional repressor, is required for TnpA binding to the TIRs of Tn5401.